Ecotourism and environmental sustainability : principles and practice - Hill, Jennifer (Jennifer Louise), 1969-; Gale, Tim (Ashgate, 2009)
Drawing on a diverse series of international case studies this book offers conceptual and practical insights into the complex interactions between ecotourism and the natural environment. The result is a critical examination of ecotourism and environmental sustainability that highlights ideas for best practice and proposes new directions for future research.